Pacing biventricular: experiência inicial - Pires, R (2001)
INTRODUCTION: Biventricular pacing has been studied for the treatment of chronic heart failure (CHF). This technique seems to be able to improve symptoms and exercise tolerance, in patients with advanced CHF and prolonged QRS duration. OBJECTIVE: To present our experience with biventricular pacing in the management of severe CHF. METHODS: Between June 2000 and March 2001, 8 patients with dilated cardiomyopathy and left bundle branch block (LBBB) were selected for transvenous biventricular pacing system implantation. Mean age: 54.12 +/- 16.8 years; 5 males. The etiology was: idiopathic in 6 cases; operated congenital heart disease in 1, and ischemic in the other. Despite tailored treatment of CHF (with all patients taking diuretics and angiotensin-converting enzyme inhibitors), 7 patients remained in NYHA class III and 1 in IV. The quality of life score (assessed by the "Minnesota living with heart failure questionnaire") was 62.25 +/- 11.29. Seven patients had sinus rhythm and only one chronic atrial fibrillation; mean PQ duration--220 +/- 76.37 ms; mean QRS duration--168.75 +/- 20.31 ms. RESULTS: Implant failure, due to coronary sinus dissection and to excessive fluoroscopy time, with no coronary sinus catheterization, occurred in 2 cases (success rate: 75%). Implant data: mean implant procedure duration: 122.5 +/- 47.82 min; mean fluoroscopy time: 35.66 +/- 22.06 min; QRS duration, after implant: 133.33 +/- 15.05 ms. Left ventricular lead final position: anterolateral in 2 patients and lateral in 4. Pacing thresholds: biventricular--1.36 +/- 0.6 V; right ventricle--0.28 +/- 0.04 V; right atrium--0.32 +/- 0.08 V. Pacing impedance (left ventricle): 1013.33 +/- 147.87 omega. Follow-up (1st and 3rd month): one patient died, suddenly, 15 days after the procedure. In the others, an improvement in the quality of life index and functional class was found. These results were independent of echocardiography data. There were no significant differences in the pacing threshold and impedance during the follow-up. CONCLUSIONS: Patients with advanced CHF and widened QRS benefited from biventricular stimulation, in which improvement on the clinical status was evident.